Evaluation of health surveillance activities of hajj 2013 in the hajj embarkation Palangkaraya - Elvan Virgo Hoesea (Jurnal Berkala Epidemiologi, 2014)
Meningococcal meningitis and Middle East Respiratory Syndrome Corona Virus (MERS-CoV) is a disease that can be transmitted to a weary pilgrim considering the high incidence of both diseases in the Middle East region. This study was conducted to evaluate the surveillance activities conducted at embarkation Palangkaraya pilgrimage between 2013 and assess the surveillance activities based on the attributes of surveillance and barriers that occur in the implementation of activities. The experiment was conducted with a descriptive design using a quantitative approach. Questionnaires were completed at 6 implementing surveillance activities. Interviews were conducted to obtain information about the variables under study includes data collection, processing, analysis and interpretation, dissemination of information, and surveillance attributes such as simplicity, flexibility, acceptability, sensitivity, positive predictive value, representative, timeliness, data quality, and data stability. Implementation of health surveillance in the hajj embarkation Palangkaraya in 2013 showed all stages of the surveillance activities have been conducted in accordance with the procedures as well as evaluating surveillance activities unless the sensitivity and positive predictive value because no cases of meningococcal meningitis. The conclusion that the implementation of health surveillance activities Hajj has been running quite a well-based approach to surveillance and surveillance attributes. The report has been used by the agency activities related to the activities of hajj embarkation.